2019
DOI: 10.4047/jap.2019.11.6.313
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of zirconia to resin: The effects of specimen preparation and loading procedure

Abstract: PURPOSEShear bond strength (SBS) test is the most commonly used method for evaluating resin bond strength of zirconia, but SBS results vary among different studies even when evaluating the same bonding strategy. The purpose of this study was to promote standardization of the SBS test in evaluating zirconia ceramic bonding and to investigate factors that may affect the SBS value of a zirconia/resin cement/composite resin bonding specimen.MATERIALS AND METHODSThe zirconia/resin cement/composite resin bonding spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, it is necessary to consider several factors in two categories: (ⅰ) the relationship between the cement and the block, and (ⅱ) the relationship between the cement and the SBS test piece. That is, there are many factors that may affect the variability and repeatability of test results 27) . In this study, we used the ultradent method to measure the SBS of resin luting cement to CAD/CAM blocks because ultradent method offers simple fabrication procedures for the bonded specimens and may reduce the influence of the two resin-cement interfaces on bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is necessary to consider several factors in two categories: (ⅰ) the relationship between the cement and the block, and (ⅱ) the relationship between the cement and the SBS test piece. That is, there are many factors that may affect the variability and repeatability of test results 27) . In this study, we used the ultradent method to measure the SBS of resin luting cement to CAD/CAM blocks because ultradent method offers simple fabrication procedures for the bonded specimens and may reduce the influence of the two resin-cement interfaces on bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…The composite resin cement, filling the larger gap between zirconia and the titanium base abutment in group D, could result in smoothening the sharp angles of the abutment surface and reduction of the stress concentration on zirconia. Chen et al 56 showed that a minimal gap (50µm) produced a higher concentration of internal stress compared to a larger gap (100µm and 180µm), hypothesizing that a thinner resin cement layer would reach the threshold of "load to failure" faster than a thicker cement layer. Other studies have shown that large cement gaps, 240µm and 500µm, also generated higher stress concentration compared to cement gaps of 96µm and 50µm, respectively 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a cement gap of approximately 100µm could minimize the increase of the internal stress [56][57][58] . It is noteworthy that the cement gap difference did not influence the debonding rate between groups B and D.…”
Section: Discussionmentioning
confidence: 99%
“…The printing supports were positioned on the non-cementing surfaces. The universal testing machine was used for reproducible loaded forces during the cementation process on all specimens (n=240) for 6 minutes ( 16 ). Microbrushes were used immediately after machine loading to eliminate excess cement to prevent adulteration of the specimen’s adhesive surfaces.…”
Section: Discussionmentioning
confidence: 99%